The effects of violent game role taking and provocation on behavioral aggression - Groves, Christopher L. (My University, 2012)
The causal relation between violent video game play and increased aggression is well established (Anderson et al., 2010; Bushman, Rothstein, & Anderson, 2010). However, the qualities of these video games and how they cultivate aggression have been largely unexplored (Anderson et al., 2010). The intent of the current study was twofold: To examine the effect of player role on behavioral aggression following violent video game play and to determine why this relation has not been discovered in other methodological contexts. Participants were randomly assigned to read brief vignettes describing their character as either deviant (invading the planet) or heroic (saving the planet). Participants were also randomly assigned to receive either low provocation or high provocation from the potential target of aggression. Further, a no-game-play condition was included to determine baseline aggression in high and low provocation conditions. It was hypothesized that individuals playing a deviant character would be more aggressive following violent video game play compared to those playing a heroic character, but only under conditions of low provocation. The results indicated that those playing as a deviant character were no more aggressive than those playing as a heroic character. This was the case in both high and low provocation conditions. Additional findings and implications are discussed.
A Thesis Submitted In Partial Fulfillment of the Requirements For the Degree of Master of Science-Psychology
Keywords: Aggressiveness; Violence in mass media; Video games psychological aspects; Video games